2009
DOI: 10.1007/s10800-008-9767-0
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of PbS multilayers on Ag(111) by ECALE

Abstract: Lead sulfide (PbS) thin films were grown on a single crystal Ag(111) substrate by Electrochemical Atomic Layer Epitaxy (ECALE) method, i.e., by alternated underpotential deposition (UPD) of lead and sulfur. The electrochemical analysis includes the investigation of the underpotential deposition processes of both Pb and S, and the characterization of deposits obtained with different deposition cycles to confirm the attainment of the right stoichiometric ratio between Pb and S. The morphological analysis has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…E-ALD technique has been successfully used to fabricate ultrathin films of metal sulfides on silver electrodes by alternating the underpotential deposition of metal and sulfur. These compounds include cadmium sulfide (CdS) [2,14,15], zinc sulfide (ZnS) [2], nickel sulfide (NiS) [4], lead sulfide (PbS) [16], copper sulfides (Cu x S) [17,18] and tin sulfides (Sn x S y ) [19]. A typical E-ALD cycle includes the underpotential deposition of sulfur followed by the surface limited reaction (SLR) of metal on S-covered Ag.…”
Section: E-ald Of Binary M X S Y Semiconductors On Ag(111)mentioning
confidence: 99%
See 1 more Smart Citation
“…E-ALD technique has been successfully used to fabricate ultrathin films of metal sulfides on silver electrodes by alternating the underpotential deposition of metal and sulfur. These compounds include cadmium sulfide (CdS) [2,14,15], zinc sulfide (ZnS) [2], nickel sulfide (NiS) [4], lead sulfide (PbS) [16], copper sulfides (Cu x S) [17,18] and tin sulfides (Sn x S y ) [19]. A typical E-ALD cycle includes the underpotential deposition of sulfur followed by the surface limited reaction (SLR) of metal on S-covered Ag.…”
Section: E-ald Of Binary M X S Y Semiconductors On Ag(111)mentioning
confidence: 99%
“…E-ALD of PbS and NiSLead sulfide (PbS) and nickel sulfide (NiS) are binary semiconductors that have received considerable attention for a variety of applications, such as detectors[23], sensing materials[24] and solar cells[25]. A complete electrochemical study of PbS multilayers has been reported by Fernandes et al[16]. The Pb ad cannot be formed on S-covered silver electrodes because of partial redissolution of sulfur.…”
mentioning
confidence: 99%
“…Indeed, we have used ECALE to successfully obtain a number of binary and ternary semiconductor thin films. These compounds include cadmium sulfide (CdS), 7-11 cadmium telluride (CdTe), 12 cadmium selenide (CdSe), 13 zinc sulfide (ZnS), 14 zinc selenide (ZnSe), 14 nickel sulfide (NiS), 15 lead sulfide (PbS), [16][17][18] copper sulfide (CuS), 19,20 and indium arsenide (InAs). 21 A specific need in our field of work is for the structural characterization-with the use of opportunistic analytical techniques-of the ultra-thin films that are obtained from the electrochemical deposition techniques.…”
Section: 1117/21201512006249 Page 2/3mentioning
confidence: 99%
“…PbS thin films have been deposited by various solution chemical method, typically including chemical bath deposition (CBD) [22][23][24][25][26][27], electrochemical deposition [28,29], spray pyrolysis [30,31], photochemical deposition [32] and successive ionic layer absorption reaction (SILAR) method [33,34]. The aqueous CBD, as a popular solution growth technique, has been developed to fabricate PbS thin films.…”
Section: Accepted Manuscriptmentioning
confidence: 99%